EDUKASI DAN KONSELING PENGGUNAAN KB IUD BAGI WUS DI DESA GARAHAN - Indaryati, Tutik (Jurnal SADEWA, 2025)
The use of long-term contraceptives such as the Intra Uterine Device (IUD) is still relatively low even though it has high effectiveness in delaying pregnancy. The low interest of women of childbearing age (WUS) in IUD birth control is influenced by a lack of knowledge, negative perceptions, and lack of partner support. This community service activity aims to increase interest in the use of birth control IUDs through providing comprehensive and educational counseling to WUS in Garahan Village, Silo District. The activity method is in the form of individual counseling and counseling with an interactive approach. The target of the activity was 97 WUS which were selected using purposive sampling techniques based on inclusion criteria. The intervention was carried out through one counseling session lasting 30 minutes which was delivered using leaflet media and direct discussions. Evaluation was carried out using pretest and posttest questionnaires to measure changes in interest before and after counseling. The results of the activity showed a significant increase in interest in using birth control IUDs after counseling interventions. Before counseling, most respondents showed low to moderate interest, but after counseling more than 76% of respondents showed high interest in using birth control IUDs. This proves that counseling is effective in raising awareness, dispelling myths, and improving attitudes towards IUD birth control. It is recommended that family planning counseling activities become a routine program that involves the active participation of health workers and families, especially couples, to support the increase in the use of long-term contraceptive methods in a sustainable manner.